The Coronary Circulation in Arterial Hypertension - Nitenberg, A.; Antony, I.; Chemla, D. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2006)
Arterial hypertension is a major coronary risk factor due to an increase prevalence of coronary atherosclerosis. On the other hand, many arguments are suggestive of symptomatic or silent episodes of
Keywords: Coronary circulation